POLYCYSTIC HORSESHOE KIDNEY WITH MEGACYSTIS AND ANHYDRAMNION AS A RARE FETAL MALFORMATION - Kocevska, Ana; Eftimova Kitanova, Aleksandra; Ajeti, Nurdzan; Tahir, Shenol; Dika, Bekim (Македонско лекарско друштво = Macedonian medical association, 2025)
Polycystic horseshoe kidney is thought to represent two separate renal diseases. Horseshoe kidney is a renal fusion anomaly during embryogenesis. Autosomal dominant polycystic kidney disease (ADPKD) is a hereditary disorder due to mutations in the genes responsible for the expression of the proteins polycystin 1 and polycystin 2. Polycystic horseshoe kidney is very rare with incidence ranges of 1 in 134 000 to 1 in 8 000 000 live births.
Keywords: polycystic kidney disease; horseshoe kidney; megacystis; anhydramnion